Increased anxiety and stress-related visits to the Shanghai psychiatric emergency department during the COVID-19 pandemic in 2020 compared to 2018–2019 - Zhang, TianHong; Chen, Zheng; Xiao, XuDong; Zhou, LinLin; Hu, YeGang; Xu, LiHua; Wei, YanYan; Tang, XiaoChen; Liu, HaiChun; Chen, Tao; Wu, HaiSu; Wu, XuMing; et al. (Frontiers in Psychiatry, 2023)
Background The coronavirus disease 2019 (COVID-19) pandemic has had a significant and far-reaching impact on mental health. The psychiatric emergency department (PED) is pivotal in the management of acute and severe mental illnesses, especially anxiety-and stress-related disorders. Aims This study aimed to evaluate whether changes in the frequency or patients’ demographics of visiting the PED occurred during the COVID-19 pandemic among individuals with anxiety and stress-related disorders. Methods This cross-sectional study used data on PED visit counts from the largest psychiatric hospital in China between 2018 and 2020 (before and during the COVID-19 pandemic). Data from 2020, representing the COVID-19 pandemic period, were extracted from electronic medical records and compared using descriptive statistics for the same periods in 2018 and 2019. Results The number of PED visits related to anxiety and stress disorders per year increased from 83 in 2018 to 136 (63.9% increase) in 2019 and 239 (188.0% increase) in 2020. Compared to that in 2018 and 2019, the proportion of PED visits in 2020 among patients with anxiety and stress disorders increased significantly. Patients with anxiety-and stress-related disorders during PED visits in 2020 were younger than those in 2018 and 2019 (three-year groups: F = 9.124, df = 2, p < 0.001). Conclusion Despite the epidemic-policy barriers against PED visits, PED care seeking has increased, thereby underscoring the need for crisis prevention services for patients with stress and anxiety disorders.